2016
DOI: 10.1104/pp.16.00211
|View full text |Cite
|
Sign up to set email alerts
|

Xylans Provide the Structural Driving Force for Mucilage Adhesion to the Arabidopsis Seed Coat

Abstract: Arabidopsis (Arabidopsis thaliana) seed coat epidermal cells produce large amounts of mucilage that is released upon imbibition. This mucilage is structured into two domains: an outer diffuse layer that can be easily removed by agitation and an inner layer that remains attached to the outer seed coat. Both layers are composed primarily of pectic rhamnogalacturonan I (RG-I), the inner layer also containing rays of cellulose that extend from the top of each columella. Perturbation in cellulosic ray formation has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
102
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(112 citation statements)
references
References 64 publications
(144 reference statements)
10
102
0
Order By: Relevance
“…The majority of PoGT61 genes showed remarkably similar profiles to the PoIRX10_2 , PoIRX10_3 , UDP-xylose synthase ( PoUXS ) and UDP-arabinose mutase ( PoUAM ) genes (Fig. 7E) that are implicated in xylan biosynthesis (Rennie and Scheller, 2014). …”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The majority of PoGT61 genes showed remarkably similar profiles to the PoIRX10_2 , PoIRX10_3 , UDP-xylose synthase ( PoUXS ) and UDP-arabinose mutase ( PoUAM ) genes (Fig. 7E) that are implicated in xylan biosynthesis (Rennie and Scheller, 2014). …”
Section: Resultsmentioning
confidence: 95%
“…These sidechains make for a more complex polysaccharide that can interact and form linkages with neighbouring polysaccharides, creating the framework that is essential for plant cell wall integrity (Cosgrove, 2005). Xylan biosynthesis occurs in the Golgi apparatus (Rennie and Scheller, 2014) where enzymes including glycosyltransferases (GTs) are required to catalyse glycosidic linkages between each monosaccharide moiety. Although a comprehensive molecular understanding is lacking, by analysing xylan deficient mutants, candidate genes involved in xylan biosynthesis have been identified (for review see Rennie & Scheller, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of UUAT1 also results in a reduction in Xyl in SM. However, this phenotype is different from the one observed for muci21 and irx14, xylosyltransferases mutants that show alterations in epidermal cell mucilage adhesion (Hu et al, 2016;Voiniciuc et al, 2015;Ralet et al, 2016). On the other hand, no Xyl (A) The uuat1-2 mutant displays early stem elongation when compared with the wild-type Col-0.…”
Section: Discussionmentioning
confidence: 96%
“…Genes in Groups II and III are all derived from plant genomes: Group II genes consist of Klebsormidium flaccidum genes, while genes in Group III consist of genes from species spanning from lower to higher land plants (Supplementary Figure S14). In this group, although no genes were definitely identified enzymatically, AT3G10320 was demonstrated as a putative xylosyltransferase which was recently characterized as MUCI21, while the genes AT3G18170 and AT3G18180 are expressed highly in a heteroxylan containing mucilaginous tissues, which indicated that the genes in this group are related to mucilage production in terrestrial plants9495.…”
Section: Resultsmentioning
confidence: 94%